Gambaran Perilaku Pencegahan HIV Pada Pasangan Serodiskordan dan Serokonkordan Di Yayasan Grapiks Bekasi Tahun 2020 - Putri, Ravinka Ayundra; Damayanti, Rita (UI Scholars Hub, 2020)
Background. HIV prevention in serodiscordant and seroconcordant couples are concerned with behaviors that focus on individual views and beliefs. Studies found that 25% were transmitted by partners who were HIV positive. Objective. This research aims to determine the description of HIV prevention behavior in serodiscordant and seroconcordant couples at the Bekasi Grapiks Foundation. Methods. This study used a case study design with a qualitative approach. Data collection by in-depth interviews via WhatsApp call. Results. Most serodiscordant and all seroconcordant partners consistently used condoms and both partners adhered to taking ARV drugs. All PLWHA disclose their status to their partners but, some disclose to their families. The relationship pattern in serodiscordant couples is the head complement, while seroconcordant couples are head complement and senior junior partner. The serodiscordant partner accepted the consequences, whereas the seroconcordant partner hoped not to be severe. Serodiscordant couples have less benefit and high resistance than seroconcordant couples. Both partners received less in-depth information about HIV/AIDS from health workers. Conclusion. There are differences in HIV prevention behavior between serodiscordant and seroconcordant couples at the Bekasi Grapiks Foundation.